EFFECT OF SPIRAPRIL ON THE LENGTH OF INTERICTAL INTERVAL IN PAROXYSMAL ATRIAL FIBRILLATION - L. N. Chikhireva; V. I. Malahov; E. S. Bykova; S. F. Sokolov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate effects of angiotensin converting enzyme inhibitor spirapril on efficacy of preventive antiarrhythmic therapy in patients with paroxysmal atrial fibrillation (AF).Material and methods. 40 patients with paroxysmal AF were involved in open-label, cross-over study with periods of antiarrhythmic drug withdrawal. During 3 months all patients received by turns two types of therapy: combination of preventive antiarrhythmic therapy with spirapril 6 mg once daily - (CT group) or preventive antiarrhythmic therapy only (AT group).Results. AF-free intervals to the first and the second AF paroxysms during antiarrhythmic drug withdrawal were comparable ) in AT and CT groups (p=0,4 and p=0,6, respectively, logrank test).Conclusion. Spirapril added to the basic preventive antiarrhythmic therapy during 3 months had no effect on the length of interictal period in paroxysmal AF.